A Novel Role for Lymphotactin (XCL1) Signaling in the Nervous System: XCL1 Acts via its Receptor XCR1 to Increase Trigeminal Neuronal Excitability. (21st May 2018) - Bird, Emma V.; Iannitti, Tommaso; Christmas, Claire R.; Obara, Ilona; Andreev, Veselin I.; King, Anne E.; Boissonade, Fiona M.
Highlights: We identified XCR1 in the peripheral and central nervous systems and demonstrated its upregulation following nerve injury. In injured nerve, XCR1 is present in nerve fibers, CD45-positive leucocytes and Schwann cells. In Vc, XCR1 labeling is consistent with expression in terminals of Aδ- and C-fiber afferents and excitatory interneurons. XCL1 increases neuronal excitability and activates intracellular signaling in Vc, a pain-processing region of the CNS. These data provide the first evidence that the XCL1-XCR1 axis may play a role in trigeminal pain pathways. Abstract: Chemokines are known to have a role in the nervous system, influencing a range of processes including the development of chronic pain. To date there are very few studies describing the functions of the chemokine lymphotactin (XCL1) or its receptor (XCR1) in the nervous system. We investigated the role of the XCL1-XCR1 axis in nociceptive processing, using a combination of immunohistochemical, pharmacological and electrophysiological techniques. Expression of XCR1 in the rat mental nerve was elevated 3 days following chronic constriction injury (CCI), compared with 11 days post-CCI and sham controls. XCR1 co-existed with neuronal marker PGP9.5, leukocyte common antigen CD45 and Schwann cell marker S-100. In the trigeminal root and white matter of the brainstem, XCR1-positive cells co-expressed the oligodendrocyte marker Olig2. In trigeminal subnucleus caudalis (Vc), XCR1 immunoreactivity was present in the outer laminae and was colocalized with vesicular glutamate transporter 2 (VGlut2), but not calcitonin gene-related peptide (CGRP) or isolectin B4 (IB4). Incubation of brainstem slices with XCL1 induced activation of c-Fos, ERK and p38 in the superficial layers of Vc, and enhanced levels of intrinsic excitability. These effects were blocked by the XCR1 antagonist viral CC chemokine macrophage inhibitory protein-II (vMIP-II). This study has identified for the first time a role for XCL1-XCR1 in nociceptive processing, demonstrating upregulation of XCR1 at nerve injury sites and identifying XCL1 as a modulator of central excitability and signaling via XCR1 in Vc, a key area for modulation of orofacial pain, thus indicating XCR1 as a potential target for novel analgesics.